Comparable Effects of Sleeve Gastrectomy and Roux-en-Y Gastric Bypass on Basal Fuel Metabolism and Insulin Sensitivity in Individuals with Obesity and Type 2 Diabetes. (21st December 2022) - Brodersen, Katrine; Nielsen, Michael F.; Richelsen, Bjørn; Lauritzen, Esben S.; Pahle, Einar; Abrahamsen, Jan; Hartmann, Bolette; Holst, Jens J.; Møller, Niels
Abstract : Aim . Bariatric surgery improves insulin sensitivity and glucose tolerance in obese individuals with type 2 diabetes (T2D), but there is a lack of data comparing the underlying metabolic mechanisms after the 2 most common surgical procedures Roux-en-Y gastric bypass surgery (RYGB) and sleeve gastrectomy (SG). This study was designed to assess and compare the effects of RYGB and SG on fuel metabolism in the basal state and insulin sensitivity during a two-step euglycemic glucose clamp. Materials and Methods . 16 obese individuals with T2D undergoing either RYGB (n = 9 ) or SG (n = 7 ) were investigated before and 2 months after surgery, and 8 healthy individuals without obesity and T2D served as controls. All underwent a 2 h basal study followed by a 5 h 2-step hyperinsulinemic euglycemic glucose clamp at insulin infusion rates of 0.5 and 1.0 mU/kg LBM/min. Results . RYGB and SG induced comparable 15% weight losses, normalized HbA1c, fasting glucose, fasting insulin, and decreased energy expenditure. In parallel, we recorded similar increments (about 100%) in overall insulin sensitivity (M -value) and glucose disposal and similar decrements (about 50%) in endogenous glucose production and FFA levels during the clamp; likewise, basal glucose and insulin concentrations decreased proportionally. Conclusion . Our data suggest that RYGB and SG improve basal fuel metabolism and two-step insulin sensitivity in the liver, muscle, and fat and seem equally favourable when investigated 2 months after surgery. This trial is registered with NCT02713555 .